2004
DOI: 10.1177/107179190401000403
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Model of Effective Knowledge Management and Directions for Future Research: Culture, Leadership, and CKOs

Abstract: Organizational culture, organizational leadership, and Chief Knowledge Officers (CKOs) each play important roles in overcoming human barriers associated with knowledge creation, transfer and sharing. This paper examines three key components of organizational culture: cooperative involvement, trust and incentives. In addition, the impact of organizational leadership on knowledge management as well as the roles and qualifications of CKOs are discussed. Through an examination of previous research and existing lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
1
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 30 publications
3
126
1
10
Order By: Relevance
“…Considering that knowledge is an important element for ensuring that employees are equipped with adequate cross-functional information and also insights derived from their external environment, Leonard-Barton (1995), Davenport and Prusak (1998), Holsapple and Joshi (2000), Ndlela and Toit (2001) and Lee and Kim (2001) advised that creating a knowledgefriendly culture is critical to ensure knowledge sharing and learning among employees. It is found that a collaborative organizational culture, enhanced by a strong sense of trust, will foster more innovation among employees as well as making them committed to their tasks (Goffee and Jones 1996;DeTienne et al 2004). Technology alone will not encourage knowledge sharing if the element of trust fails (Davenport and Prusak 1998) and an incentive system can further enhance knowledge sharing initiatives (Park 2006).…”
Section: Culturementioning
confidence: 99%
“…Considering that knowledge is an important element for ensuring that employees are equipped with adequate cross-functional information and also insights derived from their external environment, Leonard-Barton (1995), Davenport and Prusak (1998), Holsapple and Joshi (2000), Ndlela and Toit (2001) and Lee and Kim (2001) advised that creating a knowledgefriendly culture is critical to ensure knowledge sharing and learning among employees. It is found that a collaborative organizational culture, enhanced by a strong sense of trust, will foster more innovation among employees as well as making them committed to their tasks (Goffee and Jones 1996;DeTienne et al 2004). Technology alone will not encourage knowledge sharing if the element of trust fails (Davenport and Prusak 1998) and an incentive system can further enhance knowledge sharing initiatives (Park 2006).…”
Section: Culturementioning
confidence: 99%
“…Therefore, this key area includes variables such as relations and attributes of people, system incentives, organizational structure, and planning, coordinating and controlling the flow of knowledge. Additionally, some authors have divided variables such as culture to facilitate understanding which consists of collaboration, trust and learning (Lee and Choi, 2003;Detienne et al, 2004). Subsequently, some redundancies were identified and some variables were eliminated.…”
Section: Key Area: People and Organizationmentioning
confidence: 99%
“…H3 90 . Leaders have to take into account issues such as culture, structure, process, training and development.…”
Section: Knowledge Sharing Modelmentioning
confidence: 99%